Arroz e feijão no prato, inflação no bolso: Uma análise da relevância do arroz e do feijão na inflação de famílias de baixa e alta renda - Silva, Aline Franciele Bertoletti (Universidade Federal de São Carlos, 2024)
Considering the relevance that staple food products hold in the consumption basket of all Brazilians and the fact that, in the recent period, specifically between 2020 and 2022, the country experienced a significant rise in food prices, the overall objective of this present study was to quantify and analyze the relationship between the prices of two staple foods in the Brazilian consumption basket, namely rice, and beans, and the inflation index for low and high-income families. The aim was to discuss how these basic products disproportionately burden the purchasing power of families located in different income brackets. Through a literature review and econometric estimates, it was possible to identify that, for the inflation of the low-income population, the price of rice exhibits a smaller effect, while beans exert a more substantial influence. In contrast, for the wealthier population, the price of beans has a more modest contribution to their inflation, highlighting the impact of rice.
Rice and beans on the plate, inflation in the pocket: An examination of the significance of rice and beans in the inflation rates among low and high-income households
Keywords: Inflação; Arroz; Feijão; Renda; Consumo; Inflation; Food Prices; Income; Consumption; Rice and Beans; CIENCIAS SOCIAIS APLICADAS::ECONOMIA::ECONOMIA MONETARIA E FISCAL; CIENCIAS SOCIAIS APLICADAS::ECONOMIA::METODOS QUANTITATIVOS EM ECONOMIA